Development of fish liver PLHC-1 spheroids and its applicability to investigate the toxicity of plastic additives - Tiantian Wang; Judith Desmet; Elisabet Pérez-Albaladejo; Cinta Porte (Ecotoxicology and Environmental Safety, 2023)
Fish liver cell lines are valuable tools to understand the toxicity of chemicals in aquatic vertebrates. While conventional 2D cell cultures grown in monolayers are well established, they fail to emulate toxic gradients and cellular functions as in in-vivo conditions. To overcome these limitations, this work focuses on the development of Poeciliopsis lucida (PLHC-1) spheroids as a testing platform to evaluate the toxicity of a mixture of plastic additives. The growth of spheroids was monitored over a period of 30 days, and spheroids 2–8 days old and sized between 150 and 250 µm were considered optimal for conducting toxicity tests due to their excellent viability and metabolic activity. Eight-day-old spheroids were selected for lipidomic characterization. Compared to 2D-cells, the lipidome of spheroids was relatively enriched in highly unsaturated phosphatidylcholines (PCs), sphingosines (SPBs), sphingomyelins (SMs) and cholesterol esters (CEs). When exposed to a mixture of plastic additives, spheroids were less responsive in terms of decreased cell viability and generation of reactive oxygen species (ROS), but were more sensitive than cells growing in monolayers for lipidomic responses. The lipid profile of 3D-spheroids was similar to a liver-like phenotype and it was strongly modulated by exposure to plastic additives. The development of PLHC-1 spheroids represents an important step towards the application of more realistic in-vitro methods in aquatic toxicity studies.